GAMBARAN PARTISIPASI MASYARAKAT DALAM PROGRAM PENGENDALIAN VEKTOR DBD DI WILAYAH KERJA PUSKESMAS AIR DINGIN - Putri, Novia Wirna; Huvaid, Sevilla Ukhtil (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
Dengue Hemorrhagic Fever (DHF) is one of the important public health problems in Indonesia. Cases of dengue fever in the city of Padang in 2015 experienced a significant increase in the amount of 1,126 cases (IR = 124.8 per 100,000 population) with a total death of 8 people (CFR = 0.7%). The Cold Water Health Center is one of the health centers in the city of Padang with a work area that has a significant increase in dengue cases in 2015 with an IR of 361.5 per 100,000 population. The research objective was to analyze community participation in the DHF vector control program in the working area of the Cold Water Health Center in Padang City in 2018. This type of research was descriptive research. The sample is 99 people taken by proportional random sampling technique. Data analysis includes univariate analysis of community participation in vector control, namely environmental modification, environmental manipulation, physical control, chemical control, biological control and the existence of larvae. The results showed that 52.5% of respondents were larvae positive, 32.3% of respondents belonged to the bad category of environmental modification, 58.6% of respondents belong to the bad category of environmental manipulation, amounting to 30.3% of respondents classified in the bad category is physical control, 78.8% of respondents belong to the bad category of chemical control, and 35.4% of respondents belong to the bad category of biological control in the DHF vector control program in the working area of the Cold Water Health Center. It is recommended to the Air Dingin Health Center to be able to socialize to the public regarding DHF vector control programs both in aspects of environmental modification, environmental manipulation, physical, chemical and biological control.Keyword: DBD, vector, environment